Patient portal access for caregivers of adult and geriatric patients: reframing the ethics of digital patient communication. Issue 3 (18th April 2022) - Ganta, Teja; Appel, Jacob M; Genes, Nicholas
Abstract : Patient portals are poised to transform health communication by empowering patients with rapid access to their own health data. The 21st Century Cures Act is a US federal law that, among other provisions, prevents health entities from engaging in practices that disrupt the exchange of electronic health information—a measure that may increase the usage of patient health portals. Caregiver access to patient portals, however, may lead to breaches in patient privacy and confidentiality if not managed properly through proxy accounts. We present an ethical framework that guides policy and clinical workflow development for healthcare institutions to support the best use of patient portals. Caregivers are vital members of the care team and should be supported through novel forms of health information technology (IT). Patients, however, may not want all information to be shared with their proxies so healthcare institutions must support the development and use of separate proxy accounts as opposed to using the patient's own account as well provide controls for limiting the scope of information displayed in the proxy accounts. Lastly, as socioeconomic barriers to adoption of health IT persist, healthcare providers must work to ensure multiple streams of patient communication, to prevent further propagating health inequities.